2020
DOI: 10.1088/1741-2552/ab8dd6
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and coupling of fractional-order models of the motor cortex and central pattern generators

Abstract: Objective. Fractional calculus plays a key role in the analysis of neural dynamics. In particular, fractional calculus has been recently exploited for analyzing complex biological systems and capturing intrinsic phenomena. Also, artificial neural networks have been shown to have complex neuronal dynamics and characteristics that can be modeled by fractional calculus. Moreover, for a neural microcircuit placed on the spinal cord, fractional calculus can be employed to model the central pattern generator (CPG). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Next, we introduce a fractional-order neuron model. In this work, we use the Grunwald-Letnikov (G-L) fractional derivative (Lu 2019(Lu , 2020, and obtain the following fractional-order CPG model with synaptic transmission,…”
Section: Cognitive Neurodynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we introduce a fractional-order neuron model. In this work, we use the Grunwald-Letnikov (G-L) fractional derivative (Lu 2019(Lu , 2020, and obtain the following fractional-order CPG model with synaptic transmission,…”
Section: Cognitive Neurodynamicsmentioning
confidence: 99%
“…Nevertheless, although the mammalian locomotion networks have been widely studied, understanding the coupling association in these networks is still an open problem (Kiehn 2016;Roberts et al 2012). In addition, the relationship between the CPG and the motor cortex has been explored in earlier studies based on the integral-order models (Lu et al 2015;Lu and Tian 2014) and the fractional-order ones (Lu 2020). The previous investigations showed that there exists parameters space which can make the synchronization of the motor cortex optimum when the CPG is added into the motor cortex.…”
Section: Introductionmentioning
confidence: 99%
“…There is a well-established exercise of assimilating delays into dynamic systems to narrative for phenomena such as biological reaction times, finite propagation speeds, and communication delays in control systems 11 , 12 . A rich array of mathematical challenges and opportunities arises from the interaction between fractional calculus, stochasticity, and time delays 13 , 14 . As well as for theoretical purposes, understanding the behavior of FSDDS has practical applications in fields such as biology, ecology, economics, finance, and engineering 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the CPG-based method can control various forms of locomotion, perform smooth transition, and easily integrate abundant sensing signals [17,18]. Fractional calculus and the investigation of fractional-order systems have been extensively studied in the last decades [19][20][21]. Fractional central pattern generator (CPG) models for locomotion systems have been researched in the reference [22,23].…”
Section: Introductionmentioning
confidence: 99%